ISLAMIC FEFAC AS AN INTERESTING LEARNING MEDIA TO IMPROVE STUDENTS’ ENGLISH ABILITY AND DEVELOP THEIR CHARACTER VALUES IN MAN REJANG LEBONG - Paidi Gusmuliana; Eka Apriani; Asri Karolina (Jurnal Inovasi Pengabdian Masyarakat Pendidikan, 2020)
The article aims to improve students’ English ability and develop character values in MAN Rejang Lebong. The subject of Community Service was 40 (fourty) students from low economic category that studied in MAN Rejang Lebong. The result showed that the service activities have been carried out well and smoothly without any obstacles; this community service showed improvement in students’ English ability. It can be seen in the result of pre-test and post-test (65 and 79). Then, this community service is also can develop students’ character such as active, independent, brave, responsibility, discussion, polite in the classroom. Students are very enthusiastic in receiving the learning material that has been delivered by the servant; and school  plays an active role in supporting the implementation of this community service.